Upaya Meningkatkan Motivasi dan Hasil Belajar Matematika tentang Bangun Ruang melalui Penggunaan Alat Bantu Manipulatif Siswa Kelas V SD N 4 Kalikebo Trucuk Klaten - Caturwati, Nanik (Universitas Sebelas Maret, 2022)
This research is entitled Efforts to Increase Motivation and Mathematics Learning Outcomes about Building Space through the Use of Manipulative Tools. The time of the research was October 24 and 31 2021. In this research, the objects were students at SD Negeri 4 Kalikebo class V. The population was 26 students. One way that teachers can apply in teaching mathematics is by using manipulative materials. There are many benefits that can be gained from using manipulative materials. Thus, it can be concluded that the results of research carried out at SD Negeri 4 Kalikebo on mathematics subjects using manipulative aids can improve learning achievement.Keywords: Learning outcomes, building space, manipulative aids